2014
DOI: 10.1038/ngeo2318
|View full text |Cite
|
Sign up to set email alerts
|

Ocean rises are products of variable mantle composition, temperature and focused melting

Abstract: Ocean ridges, where Earth's tectonic plates are pulled apart, vary from more than 5-km depth in the Arctic to 750 m above sea level in Iceland. This huge relief is generally attributed to mantle plumes underlying mantle hotspots, areas of enormous volcanism marked by ocean islands. The plumes are thought to feed the mantle beneath adjacent ocean ridges. This results in thickened crust and ridge elevation to form ocean rises. The composition of mid-ocean ridge basalt, a direct function of mantle composition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…A key factor controlling the variability of the oceanic crust might be mantle temperature (Klein and Langmuir, 1987;Dalton et al, 2014;Dick and Zhou, 2014). One of the best-documented features is that crust formed near hotspots is generally thicker than crust formed away from hotspots (e.g., White et al, 1992;Korenaga et al, 2002).…”
Section: Thickness Of Oceanic Crust Ad 1992mentioning
confidence: 99%
“…A key factor controlling the variability of the oceanic crust might be mantle temperature (Klein and Langmuir, 1987;Dalton et al, 2014;Dick and Zhou, 2014). One of the best-documented features is that crust formed near hotspots is generally thicker than crust formed away from hotspots (e.g., White et al, 1992;Korenaga et al, 2002).…”
Section: Thickness Of Oceanic Crust Ad 1992mentioning
confidence: 99%
“…For clarity, in this paper, unless otherwise stated, peridotite is used to refer to olivine‐rich lithologies, including dunite, harzburgite, lherzolite, wehrlite, and any transitional lithologies between these; mafic rock or lithology is used to refer to olivine‐poor and olivine‐free lithologies, including olivine pyroxenite, garnet pyroxenite, clinopyroxenite, hornblendite, eclogite, and any transitional lithologies between these. The mineralogical and compositional heterogeneities in the lithosphere and/or the asthenosphere have been widely used to explain the petrological and geochemical diversity of mantle‐derived rocks (e.g., Allegre & Turcotte, ; Dick & Zhou, ; Halliday et al, ; Herzberg, ; Hirschmann & Stolper, ; Hofmann & White, ; Kogiso et al, ; Lambart et al, ; Lustrino, ; Niu & O'Hara, ; Pilet et al, ; Sobolev et al, ; Yang & Zhou, ) and may also contribute to the seismic velocity variations in the upper mantle (e.g., Anderson & Bass, ; Bruneton et al, ; Chen et al, ; Eeken et al, ; Foulger et al, ). However, the geochemistry of either basalts or olivine phenocrysts that is used to argue for source lithological and/or compositional heterogeneities is to some extent compromised by variations in intensive parameters such as temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Much experimental work on the partial melting of a variety of peridotitic and mafic rocks has been carried out over the past several decades (e.g., Green, ; Kogiso et al, ; Kushiro, ; Lambart et al, ; Wyllie, and references therein), providing a fundamental experimental basis for understanding how the P‐T‐X (i.e., pressure, temperature, and composition) of mantle‐derived magmas vary and are related to each other (e.g., Ghiorso et al, ; Hirschmann et al, ; Lambart et al, ). However, the relationship between the major element patterns of basaltic melts and lithological and/or compositional variations in source materials is still unclear because the major element characteristics of basaltic melts are strongly affected not only by source composition, melting temperature, and pressure but also by magmatic processes such as fractional crystallization and magma mixing (e.g., Dick & Zhou, ; Herzberg & O'Hara, ; Jennings et al, ; Kushiro, ; Lambart et al, ; Langmuir et al, ; Niu et al, ; Putirka et al, ; Yang et al, ). Partial melting experiments suggest that peridotitic rocks with Mg# (MgO/(MgO + FeO), molar ratios) ranging from 0.85 to 0.9 at different pressures can produce melts that evolve to primitive MORB (middle ocean ridge basalt) when different degrees of olivine fractionation occur (e.g., Hirose & Kushiro, ; Kushiro, ).…”
Section: Introductionmentioning
confidence: 99%
“…The preferential melting of pyroxenite and eclogite will mess up to estimate the thickness of oceanic crust. Moreover, remelting a previously depleted source would also yield low melt volumes, low sodium basalts, highly incompatible element depleted peridotites, and thin crust Dick and Zhou, 2015;Niu, 2004). In the last two decades, Re-Os isotopic studies have indicated that some abyssal peridotites may have experienced multiple ancient melt extraction episodes (Alard et al, 2005;Brandon et al, 2000;Harvey et al, 2006;Ishikawa et al, 2011;Lassiter et al, 2014;Liu et al, 2008;Roy-Barman and Allègre, 1994), and some trace element variations in MORB can only explained by a previously depleted source (Hofmann, 1997).…”
Section: Introductionmentioning
confidence: 99%